2012
DOI: 10.1088/0004-637x/752/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Possible Disintegrating Short-Period Super-Mercury Orbiting Kic 12557548

Abstract: We report here on the discovery of stellar occultations, observed with Kepler, that recur periodically at 15.685 hour intervals, but which vary in depth from a maximum of 1.3% to a minimum that can be less than 0.2%. The star that is apparently being occulted is KIC 12557548, a V = 16 magnitude K dwarf with T eff,s 4400 K. The out-of-occultation behavior shows no evidence for ellipsoidal light variations, indicating that the mass of the orbiting object is less than ∼3 M J (for an orbital period of 15.7 hr). Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
395
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(418 citation statements)
references
References 56 publications
22
395
1
Order By: Relevance
“…In all three cases, the long egress was interpreted as a comet-like tail trailing the transiting object (Rappaport et al 2012;Budaj 2013;Vanderburg et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…In all three cases, the long egress was interpreted as a comet-like tail trailing the transiting object (Rappaport et al 2012;Budaj 2013;Vanderburg et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Recent inferences of disintegrating exo-mercuries in close-in orbits have also used volcanic outgassing as a possible means to inject dust into the planetary atmosphere before being carried away by thermal winds (e.g. Rappaport et al 2012Rappaport et al , 2014. However, whereas extremely small planets (nearly Mercury-size) subject to intense irradiation can undergo substantial mass loss through thermal winds, super-Earths are unlikely to undergo such mass-loss due to their significantly deeper potential wells (Perez-Becker & Chiang 2013;Rappaport et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Higher cadence ground-based follow-up photometry revealed several sets of asymmetric transits with varying depths (of up to 40%) at an orbital period of ≈ 4.5 hours, but with highly inconsistent transit times . Asymmetric transit shapes and variable transit depths have come to be associated with disintegrating planets transiting main sequence stars (Rappaport 2012(Rappaport , 2014Sanchis-Ojeda 2015), and Vanderburg et al (2015) interpreted the observations of WD 1145+017 as being caused by a similar phenomenon. Vanderburg et al (2015) showed that a dust cloud formed from material sublimated off several fragments of a large, tidally disrupted asteroid (with roughly the mass of Ceres) occulting the star could plausibly explain the observed transits.…”
Section: Introductionmentioning
confidence: 99%